Experimental and numerical investigations on slender panels with holes under symmetrical localised loads. (1st February 2021) - Maiorana, E.; Tetougueni, C.D.; Zampieri, P.; Pellegrino, C.
Highlights: Plate slenderness strongly influences the post-critical behaviour of steel girder. The existing standard formulas are conservative and need to be updated. FEM analysis is sensitive to the geometrical imperfections and residual stresses. Perforated beams are less resistant to compressive force than normal girders. Abstract: Perforated steel girders under a single or combined in plane loading have been largely studied in the literature. However, such investigations were trusted on the numerical modelling and FEM analysis and due to the lack of experimental results in most cases, the accuracy of the numerical model and the consideration of imperfections in the FEM analyses are open to reflexion. In this paper, a series of experimental tests are performed to study the post-critical behaviour of perforated steel girders. Ten full scales steel girders were tested under uniaxial compressive force. Amongst them, four were used as control specimens whereas a circular hole was located in the center of the other six. The parameters such as the geometry of the web plate, the position of the hole and the plate slenderness are found as those most influencing the post-critical behaviour. Finally, the experimental results were used to validate the intensive numerical analyses. The results obtained showed the strong influence of combined geometrical imperfections and residual stresses on the mid-plane Von Mises stresses.